Сказка для влюбленных: [роман] / Х. Нортон - Нортон Хельга (Панорама романов о любви, 2005)
Экземпляры: ЧЗ (20181126) / Инвентарный номер: 40003 / Цена: 30 / Авт.знак: Н 83 / ГРНТИ: 17.82 / ББК: 84(4Англ)